Solve for z (6+z)/10=-2

Math
6+z10=-2
Multiply both sides of the equation by 10.
10⋅6+z10=10⋅-2
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 10.
Tap for more steps…
Cancel the common factor.
10⋅6+z10=10⋅-2
Rewrite the expression.
6+z=10⋅-2
6+z=10⋅-2
Multiply 10 by -2.
6+z=-20
6+z=-20
Move all terms not containing z to the right side of the equation.
Tap for more steps…
Subtract 6 from both sides of the equation.
z=-20-6
Subtract 6 from -20.
z=-26
z=-26
Solve for z (6+z)/10=-2

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top